Peran Pemimpin Adat dalam Mempertahankan Civic Commitment: Studi Kasus di Kampung Naga - Iis Siti Sholehah; Iim Siti Masyitoh; Sri Wahyuni Tanshzil (Program Studi Pendidikan Sejarah - Universitas Samudra, 2025)
This study aims to analyze the role of traditional leaders in maintaining the civic commitment of the Kampung Naga indigenous community amid the challenges of globalization and modernization. A qualitative case study method was employed through field observation, in-depth interviews, and document analysis. The findings reveal that the kuncen, punduh, and lebe hold strategic roles as preservers of traditional values, social mediators, and guardians of community harmony. Their leadership aligns with Mintzberg’s leadership role theory, covering interpersonal, decision-making, and informational functions. These roles contribute to realizing key indicators of civic commitment, such as civic identity, collective efficacy, future civic engagement, community problem-solving, and civic actions. Thus, traditional leaders play a vital role in ensuring the continuity of local traditions while strengthening the civic commitment of the Kampung Naga community. This commitment serves as a cultural safeguard to help the community face the pressures of modernization without losing its cultural identity.